Samoa : Livestock Production and Marketing - World Bank (Washington, DC, 2013)
This report was prepared to provide information and analysis of the Samoan livestock sub-sector for the Ministry of Agriculture and Fisheries through a technical assistance assignment financed by the World Bank. The Word Bank contributed technical assistance support to the Government of Samoa to help identify measures to strengthen agriculture sector institutions, to improve the performance of selected commodities - including in the livestock sector - both in terms of import substitution and export expansion, and to identify strategic agriculture infrastructure investments. This report provides information and analysis on livestock inventories, the competitiveness of Samoan livestock products, livestock slaughtering and meat hygiene, and government policies and institutional frameworks needed to enhance the competitiveness of domestic livestock production. The report also contains recommendations for the development of a livestock component as part of the proposed Samoa Agriculture Competiveness Enhancement Project (SACEP).